Views of patients and professionals about electronic multicompartment medication devices: a qualitative study. Issue 10 (17th October 2016) - Hall, Jill; Bond, Christine; Kinnear, Moira; McKinstry, Brian
Abstract : Objectives: To explore the perceived acceptability, advantages and disadvantages of electronic multicompartment medication devices. Design: Qualitative study using 8 focus groups and 10 individual semistructured interviews. Recordings were transcribed and analysed thematically. Strategies were employed to ensure the findings were credible and trustworthy. Participants and setting: Community pharmacists (n=11), general practitioners (n=9), community nurses (n=12) and social care managers (n=8) were recruited from the National Health Service (NHS) and local authority services. Patients (n=15) who were current conventional or electronic multicompartment medication device users or had medication adherence problems were recruited from community pharmacies. 3 informal carers participated. Results: Electronic multicompartment medication devices which prompt the patient to take medication may be beneficial for selected individuals, particularly those with cognitive impairment, but who are not seriously impaired, provided they have a good level of dexterity. They may also assist individuals where it is important that medication is taken at fixed time intervals. These are likely to be people who are being supported to live alone. No single device suited everybody; smaller/lighter devices were preferred but their usefulness was limited by the small number/size of storage compartments. Removing medications was often challenging. Transportability was an important factor for patients and carers. A carer's alert if medication is not taken was problematic with multiple barriers to implementation and no consensus as to who should receive the alert. There was a lack of enthusiasm among professionals, particularly among pharmacists, due to concerns about responsibility and funding for devices as well as ensuring devices met regulatory standards for storage and labelling. Conclusions: This study provides indicators of which patients might benefit from an electronic multicompartment medication device as well as the kinds of features to consider when matching a patient with a device. It also highlights other considerations for successful implementation including issues of responsibility, regulation and funding.